1999
DOI: 10.1021/bi990744t
|View full text |Cite
|
Sign up to set email alerts
|

Monomer−Dimer Equilibrium Constants of RNA in the Dimer Initiation Site of Human Immunodeficiency Virus Type 1

Abstract: The genome of the human immunodeficiency virus (HIV) exists as a dimer of two identical RNA molecules hydrogen bonded to each other near their 5' ends. The dimer, known to be important for viral infectivity, is formed by two monomers interacting through a stem-loop structure called the dimer initiation site (DIS). An initially formed intermediate, the "kissing" dimer, is unstable and rearranges to the stable, duplex form. In this report we use nondenaturing polyacrylamide gel electrophoresis to measure the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
(44 reference statements)
1
17
1
Order By: Relevance
“…Interestingly, TAR annealing is ∼10-fold slower than mini-TAR annealing in the absence of protein chaperone 30. We hypothesize that this is due to the larger entropy loss upon intermediate complex formation in the case of the longer hairpins 44. Alternatively, slower annealing of longer hairpins may be due to a greater electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 90%
“…Interestingly, TAR annealing is ∼10-fold slower than mini-TAR annealing in the absence of protein chaperone 30. We hypothesize that this is due to the larger entropy loss upon intermediate complex formation in the case of the longer hairpins 44. Alternatively, slower annealing of longer hairpins may be due to a greater electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 90%
“…The fact that this difference between mini and full-length TAR hairpins does not disappear in higher salt suggests that the difference is not due to the stronger electrostatic repulsion between the longer molecules. Shubsda et al also observed slower association of longer hairpins, and attributed this difference to the larger entropy loss upon complex formation 73.…”
Section: Resultsmentioning
confidence: 97%
“…Tight dimers withstand dissociation during semi-native gel electrophoresis (Tris-borate EDTA (TBE) buffer at 26°C). By contrast, loose dimers are detected only by using native conditions, since they dissociate upon loading in semi-native TBE/26°C gels [33]. Loose dimers are thought to correspond to a loop-loop interaction between two SL1 motifs, whereas tight dimers are thought to represent a more extensive SL1–SL1 interaction due to the intra- to intermolecular conversion of the stems located below the SL1 loop ([2,4]).…”
Section: Resultsmentioning
confidence: 99%